Pengaruh Kenaikan Harga Rokok Dan Pendapatan Uang Saku Terhadap Konsumsi Rokok Harian Mahasiswa Fakultas Pertanian Universitas Sultan Ageng Tirtayasa - Aliudin; Ningrum, Loka Ayu Sri Kusuma; Sinaga, Sintia Frisma; Aprilianti, Risna; Rifqy Hafizh; Arroisi, Subhan Nurhaqiarso; Ramadhani, Fahriza; Widodo, Akbar Wahyu; Hidayat, Alif; Ilham, Gymnastiar (Cattleya Darmaya Fortuna, 2024)
This research was carried out to analyze how the influence of increases in cigarette selling prices and monthly pocket money affects monthly cigarette consumption among students. The method applied in this research is the multiple linear regression method. The data used in this research is primary data obtained from the results of a campus survey at Sultan Ageng Tirtayasa University. The data collection technique was purposive sampling with a total of 60 students as respondents. Data on the characteristics of respondents in this study include the brand and selling price of cigarettes (Independent Variable X1), Monthly Pocket Money (Independent Variable X2), and monthly cigarette consumption behavior (Dependent Variable Y). Based on the results of multiple linear regression analysis, it can be concluded that cigarette prices have a significant influence on monthly cigarette consumption behavior, while monthly pocket money income does not have a significant influence on students' monthly cigarette consumption behavior.